Determination of cloud and precipitation characteristics in the monsoon region using satellite microwave and infrared observations - LIU, GUOSHENG (MAUSAM, 2003)
We have studied the cloud and precipitation features in the Indian summer monsoon region based on satellite microwave and infrared observations. Emphases are particularly given to the differences between stratiform and convective rains and between rains over land and over ocean. In the studied region, average rainfall rate of convective clouds is about 6 times higher than for stratiform clouds while the latter covers 4 to 5 times more area than the former. As a result, convective rains produce higher rain total than stratiform rains with a ratio of about 3 : 2. The difference between convective and stratiform rains is evident virtually by any satellite signatures – cloud top temperature, and microwave emission, scattering and combined signatures. Cloud top temperature appears no skill to reflect surface rainfall rates for stratiform rains while colder cloud top temperatures correspond to higher rainfall rates for convective clouds. As rainfall rate increases, microwave emission signature reaches saturation much quicker for stratiform rains than for convective rains. For convective rains, the rainfall rate – scattering signature relation shows a distinct difference between rains over land and over ocean. Corresponding to the same rainfall rate, the scattering signature over land is about twice as high as that over ocean. The mean vertical precipitation profiles showed that stratiform rains have a constant rainfall rate below freezing level and a sharp drop-off above, regardless over land or ocean. Convective rain profiles, on the other hand, often have the maximum rainfall rate below the freezing level, implying a significant growth of raindrops by warm microphysical processes, such as coalescence. It is also found that given the same surface rainfall rate, the amount of ice particles above freezing level is substantially greater for convective rains over land than over ocean, which explains the difference of scattering signatures between rains over the two different surface types. It is also demonstrated that the sub-pixel variability of rains is largely responsible for the mismatch between plane-parallel model simulations and actual satellite observations.